Integrated ecological and technological approaches for nutrient removal from anthropogenically polluted surface water: a case study of Burgas Lake (Vaya Lake) - Syulekchieva, Diana; Midyurova, Blagovesta; Koleva, Elena (Ecological Questions, 2026)
Declining water availability, eutrophication and increasing anthropogenic pressure on aquatic ecosystems highlight the need for sustainable approaches for nutrient reduction and safe water management. This study evaluates a pilot, multi-stage filtration system as a possible additional step for the further treatment of water. Two experimental filtration units were tested with water from Burgas Lake (Vaya Lake), as the lake is highly anthropogenically polluted: a filter containing natural zeolite (clinoptilolite) and a filter with biomass from the macrophyte Stuckenia pectinata. After 60 minutes of recirculation, a reduction of TN (Total Nitrogen) to 67-76%, of N-NO₃ (Nitrogen Nitrate) to 19-38% and of PO₄³- P (Orthophosphate) to 58-66% was observed. The results show that both nature-based filtration media effectively reduce nitrogen and phosphorus compounds under controlled laboratory conditions, with a higher nutrient removal efficiency observed for the Stuckenia pectinata filter. The proposed pilot system can serve as a preliminary modelling framework for further treatment of anthropogenically polluted surface waters and for future development of risk-based water management approaches.